Mutations in a putative global transcriptional regulator cause X-linked mental retardation with alpha-thalassemia (ATR-X syndrome). - Gibbons, R; Picketts, D; Villard, L; Higgs, D (1995)
The ATR-X syndrome is an X-linked disorder comprising severe psychomotor retardation, characteristic facial features, genital abnormalities, and alpha-thalassemia. We have shown that ATR-X results from diverse mutations of XH2, a member of a subgroup of the helicase superfamily that includes proteins involved in a wide range of cellular functions, including DNA recombination and repair (RAD16, RAD54, and ERCC6) and regulation of transcription (SW12/SNF2, MOT1, and brahma). The complex ATR-X phenotype suggests that XH2, when mutated, down-regulates expression of several genes, including the alpha-globin genes, indicating that it could be a global transcriptional regulator. In addition to its role in the ATR-X syndrome, XH2 may be a good candidate for other forms of X-linked mental retardation mapping to Xq13.